Environmental and Social Impact Analysis of the Development of the Mrican Baru Final Disposal Site (TPA) in Ponorogo Regency - Aliyadi; Kumalasari, Ellisia; Putra, Wawan Trisnadi (Jurnal Ar Ro'is Mandalika (Armada), 2026)
The issue of waste management in Ponorogo Regency is becoming increasingly complex as waste generation rises and the capacity of the existing Final Disposal Site (TPA) is limited. The development of the Mrican Baru TPA with a sanitary landfill system is planned as a long-term solution, but it has the potential to cause environmental and social impacts. This study aims to analyze the environmental conditions and the social perceptions of the community regarding the planned development of the Mrican Baru TPA. The research method used is quantitative with a descriptive-analytic approach. Data was collected through environmental quality measurements (water and air), distribution of questionnaires to surrounding communities, and the review of UKL-UPL documents and operational data from the Environmental Agency. The results show that the existing environmental quality conditions are still below environmental standards; however, there is potential for increased environmental pressure during the operational phase of the TPA. Community perceptions of the TPA development are moderately accepting, with the condition of strict environmental management and transparency of information. This study recommends strengthening the environmental monitoring system and enhancing community participation to ensure the sustainability of TPA operations.